E. Tzili-Apango (2018). El camino al Siglo del Pacífico. Las otras rutas de la seda del siglo XXI. México: Palabra de Clío. 200 pp. - Calderón García, Michelle (Estudios de Asia y África, 2019)
E. Tzili-Apango (2018). El camino al Siglo del Pacífico. Las otras rutas de la seda del siglo XXI. México: Palabra de Clío. 200 pp.